ANALISIS KEPUASAN MAHASISWA UNIVERSITAS PADJADJARAN DALAM MENGKONSUMSI PRODUK RICHEESE FACTORY - Eka Purna Yudha; Rezky Algipari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study aims to determine and analyze the attributes that affect the satisfaction and level of importance of Richeese Factory's customers. The sample in this study consisted of 40 people who were Agribusiness Students at Padjadjaran University. Primary data collection was done using a questionnaire using the google form feature as measured by a Likert scale. Secondary data obtained from the internet related to research. The method used in this research is descriptive. The data analysis technique uses the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) through Microsoft Excel Software. The results showed that the level of satisfaction of UNPAD Agribusiness Students who bought Richeese Factory products was 84.55% which was included in the "very satisfied" category.